Sistem Penentuan Prioritas Penerima Rehab Rumah Dhuafa Menggunakan Metode TOPSIS Berbasis Web - Novia Hasdyna; Teuku Irfan Fajri; Muhammad Jabar (Faculty of Computer Science, University of Jember, 2023)
The process of selecting candidates for home rehabilitation of Dhuafa in Desa Ulee Nyeue, Kec. Banda Baro, Aceh Utara still using a manual process and by a subjective assessment. In this study the authors designed a decision support system to determine the candidates for home rehabilitation of Dhuafa in Desa Ulee Nyeue, Kec. Banda Baro using TOPSIS method. The criteria we used in the decision support system process are the area of the house, house building materials, type of floor, occupation and income. In this decision support system, it is supported by a method in making decisions, that is a web- based Topsis method which can support data processing. The sample data analyzed by using Topsis method in this research obtained that several people who had the priority to receive the housing rehabilitation of dhuafa assistance based on the preference value of each alternative are Fatimah Ben, which has a value of 0.534110001, Habsah with a value of 0.481135666 and Mawardi with a value of 0.629027038. Habsah with a value of 0.481135666 and Mawardi with a value of 0.629027038. The final result of this research is that the system built can help the selection team for home rehabilitation of dhuafa in Desa Ulee Nyeue, Kec. Banda Baro, Aceh Utara to make the process of determining more accurate.